An Analysis of Students’ Learning Independence in Learning English for Computer Using Google Classroom - Dharmawati Dharmawati (Budapest International Research and Critics University, 2021)
This research aims to know independent learning of English for Compute in using Google Classroom during the COVID-19 pandemic. The method used of this research was elaborating from quantitative and qualitative descriptive. The population was Informatics students in the first semester at Universitas Harapan Medan. Sampling techniques used random sampling with a research sample of 65 students of 1-1 and 1-2 classes. Data collection techniques used triangulation: questionnaires, interviews and observations. The results showed that the average level of student learning independence using google classroom in learning English for Computer during COVID-19 pandemic was very high at the average value of indicators: self-confidence (82.62), sel-discipline (85.51), initiative (82.34), responsibility (84.92), motivation (86.27), then the average indicator of independent learning is 84.33. From these results knows that the scale range of the criteria for the score of the respondent's level of achievement, then the interpretation of learning independence in learning English for computer for Informatics students using Google Classroom during the Covid 19 pandemic is very high.